Supercapacitor behavior and characterization of RGO anchored V2O5 nanorods - Govindarajan, D.; Uma Shankar, V.; Gopalakrishnan, R. (Journal of materials science. Materials in electronics, 2019)
Reduced graphene oxide (RGO) anchored vanadium pentoxide (V 2 O 5 ) nanorods have been synthesized by using simple and cost efficacious sol–gel method. The prepared sample was analyzed by different physical and electrochemical techniques such as TG/DTA, XRD, XPS, FTIR, Micro-Raman, FESEM, HRTEM and cyclic voltammetry and galvanostatic charge/discharge. The electrochemical characterization shows that all the curves exhibit quasi-rectangular shape with redox peak, which indicates the pseudocapacitance nature of the V 2 O 5 and RGO/V 2 O 5 electrode materials. V 2 O 5 electrode material exhibits the high specific capacitance (112 F/g) at low scan rate (10 mV/s) due to high surface area. The RGO/V 2 O 5 electrode material exhibits two folds greater specific capacitance values (218.4 F/g at 10 mV/s) than pure V 2 O 5 electrode material. This result clearly indicates the pseudocapacitance nature was enhanced by the RGO nanosheets. The GCD curve also reveals the RGO/V 2 O 5 electrode has good charge/discharge time and superior specific capacitance than bare V 2 O 5 electrode. These excellent electrochemical activities may credit due to RGO nanosheets, which induce large transfer of electrons and also provides high surface sites and short transport path length for the diffusion of electrolyte ions.